2015
DOI: 10.1111/cob.12104
|View full text |Cite
|
Sign up to set email alerts
|

The eating‐related behaviours, disorders and expectations of candidates for bariatric surgery

Abstract: It is important that clinicians and researchers understand the possible eating-related difficulties experienced by pre-bariatric surgery candidates, as well as their expectations of how their eating and hunger will change after surgery. This review examines English-language publications related to the eating-related behaviours, disorders and expectations of bariatric candidates. Seventy-five articles related to binge eating disorder, grazing, night eating syndrome, emotional eating, food cravings and addiction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 114 publications
(370 reference statements)
1
46
0
6
Order By: Relevance
“…Because of the differences of diagnostic criteria and assessment methods in studies, the prevalence of NES in bariatric surgery is 2-55%. 18 The prevalence of NES was found 2-20% in studies, made by using stricter diagnostic criteria in bariatric surgery samples. 4,5 In addition, studies suggest comorbidity with NES and BED partly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the differences of diagnostic criteria and assessment methods in studies, the prevalence of NES in bariatric surgery is 2-55%. 18 The prevalence of NES was found 2-20% in studies, made by using stricter diagnostic criteria in bariatric surgery samples. 4,5 In addition, studies suggest comorbidity with NES and BED partly.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates of BED (27-49%) were high for patients undergoing bariatric surgery. [17][18][19] According to a new meta-analysis, the prevalence of BED (based on random effects) among patients seeking and undergoing bariatric surgery was 17%. 20 The prevalence of BED in our study was 11.1%.…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is higher in some specific populations. The syndrome is found in 2 to 20% of the morbidly obese candidates for bariatric surgery 12 , in 8 to 25% of psychiatric patients 13 , and in 8.6% of patients with sleep apnea 14 . University students are exposed to several factors that could favour NES development.…”
mentioning
confidence: 99%
“…Previous studies showed that differences exist examining eating behaviours, emotional regulation and the response to food stimuli [47][48][49][50][51]. In this study we selected obese subjects with gorging and snacking behavior that can, in a continuous spectrum, be regarded as subjects with low psychopathology in all obese mental dimensions such as body image, mood and anxiety [28,29] (Table 4).…”
Section: Discussionmentioning
confidence: 99%